Perancangan Sistem Kontes Burung Kicau Berbasis Website dengan Metode Human Centered Design - Viviana Hanifa; Savitri (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2026)
Abstract – This study aims to develop a web-based bird song contest system to enhance scoring transparency and administrative efficiency at Gantangan Kampung Jati. The main issue addressed is the manual scoring process, which often leads to unclear results and reduced participant trust. This research employs the Human-Centered Design (HCD) method, emphasizing user needs throughout the system development process. Data were collected through observation, interviews, and questionnaires involving contest organizers, judges, and participants. The developed system includes judge score input, automatic result recapitulation, and both manual and online payment features. System testing was conducted using Black Box Testing and White Box Testing methods. The results indicate that the system functions as intended and achieved a user evaluation score of 86.03%, categorized as very good. Based on these findings, it can be concluded that the proposed system effectively improves scoring transparency, administrative efficiency, and participant trust in bird song contests.